The mutational landscape and actionable targets of gallbladder cancer: an ancestry-informed and comparative analysis of a Chilean population - Erices, José Ignacio; González, Evelin; Salgado, Marcela; Barahona-Ponce, Carol; Freire, Matías; Sepúlveda-Hermosilla, Gonzalo; Ampuero, Diego; Blanco, Alejandro; Gárate-Calderón, Valentina; Báez-Benavides, Pablo; Tapia-Valladares, Camilo; Toro, Jessica; et al. (Frontiers in Oncology, 2025)
IntroductionGallbladder cancer (GBC) is a highly aggressive malignancy with one of the highest incidence rates reported in Chile. Despite its clinical impact, molecular characterization of GBC in Latin American populations remains limited, and the absence of effective targeted therapies underscores the urgent need for new therapeutic strategies.MethodsWe collected 118 tumor samples, of which 56 passed sequencing quality control using the Oncomine™ Comprehensive Assay v1. Somatic variants were identified with ANNOVAR and Cancer Genome Interpreter, and ancestry was inferred using ADMIXTURE and PCA with ancestry-informative markers. Comparative analyses were performed with Japanese, Singaporean, and U.S. cohorts.ResultsA total of 535 somatic mutations were detected in 43 genes, with TP53 (30%), TSC2 (29%), and NOTCH1 (27%) being the most frequently mutated. We identified 121 clinically actionable variants in ATM, BRCA1/2, EGFR, ERBB2, and other genes. Exploratory analysis suggested an association between higher Mapuche ancestry and TP53 mutations. Comparative analyses revealed distinct mutational patterns in the Chilean cohort relative to Asian and U.S. datasets.ConclusionThis ancestry-informed genomic analysis provides the first comprehensive landscape of Chilean GBC, identifying actionable alterations with potential therapeutic relevance and supporting the development of population-specific precision oncology strategies.